A Preliminary Note on the Return of Nutrient by the Leaf-litter of Wet (Montane) Temperate Evergreen Shola Forests of Nilgiris - Venkataramanan, C.; Chinnamani, S. (Indian Forester, 1978)
Preliminary studies on the chemical composition and total quantity of the leaf litter in the wet (montane) temperate evergreen forests (locally called as Sholas ) of the Nilgiris in Tamil Nadu State, has been attempted. Shola forelts of Nilgiris add annually 2121 kg/ha of litter, which by way of nutrients works out to annual addition of 23 kg N/ha, 1.3 kg P/ha; 11 kg K/ha, 34 kg Ca/ha and 5 kg Mg/ha in addition to 1956 kg organic matter/ ha containing all important micro-nutrients. In terms of money value, addition or nutrients works out to be about Rs. 4300/ha/annum. This recycling of nutrient in Sholas keeps the forest under high fertility status with rich top soil and dense vegetation. Thus, there is no erosion problem in protected Sholas. They provide perennial unpolluted, crystal-clear water to the hill stream of Nilgiris and various villages and towns are dependent on these streams. Hence, it is absolutely necessary to protect these Sholas as they are protective in nature and are of paramount importance for soil and water conservation in the hills and in addition they are our national assets with aesthetic, recreational and anti-pollution value.